Severe sepsis criteria, PELOD-2, and pSOFA as predictors of mortality in critically ill children with sepsis - Anindita Wulandari; Pudjiastuti Pudjiastuti; Sri Martuti (Paediatrica Indonesiana, 2019)
Background Sepsis is one of the main causes of death in infants and children. Currently, it is defined as a life-threatening organ dysfunction, caused by an inflammatory response of infection. Several organ dysfunction assessment methods are available, but they are not uniformly used. Objective To compare the accuracy of three mortality predictor tools: severe sepsis criteria, pediatric logistic organ dysfunction (PELOD)-2, and pediatric sequential organ failure assessment (pSOFA), in critically ill children with sepsis. Methods This prospective cohort study was conducted in the pediatric intensive care unit (PICU) and pediatric high care unit (HCU) of dr. Moewardi Hospital, Surakarta, Central of Java. All patients who met the systemic inflammatory response syndrome (SIRS) criteria were included in our study. The exclusion criteria were congenital anomalies of heart or kidney, malignancy, or hematological abnormalities. The data were taken from laboratory and physical examinations by the physicians on duty. The outcome assessed was mortality. Results Of 30 subjects, the mean age was 22.22 (SD 29.36) months; the most common infection source was the respiratory tract, followed by gastrointestinal tract and central nervous system. Most subjects were treated in the PICU and had a mean length of stay of 8.70 (SD 11.91) days. Severe sepsis and PELOD-2 were not significant predictors of death. However, pSOFA score was a statistically significant predictor of mortality, with odds ratio 10.11 (95%CI 1.054 to 97.002; P=0.039). Conclusion Pediatric SOFA (pSOFA) is a better predictor of mortality compared to PELOD-2 and SIRS-severe sepsis. A pSOFA score â‰¥ 2 increases the risk of mortality by 10.11-fold.